Come-back of phenanthridine and phenanthridinium derivatives in the 21st century - Tumir, Lidija-Marija; Radić Stojković, Marijana; Piantanida, Ivo (Beilstein Journal of Organic Chemistry, 2014)
Phenanthridine derivatives are one of the most intensively studied families of biologically active compounds with efficient DNA binding capability. Attracting attention since DNA structure discovery (1960s), they were early recognized as a symbol of DNA intercalative binding, for many decades applied as gold-standard DNA- and RNA-fluorescent markers (ethidium bromide), probes for cell viability (propidium iodide), but also “ill-famed” for various toxic (genotoxic) and mutagenic effects. After two decades of low interest, the discovery of phenanthridine alkaloids and new studies of antiparasitic/antitumor properties of phenanthridine derivatives resulted in the strong increase of the scientific interest about the turn of this century. Here are summarized phenanthridine-related advances in the 21st century (2000-present period) with emphasis on the supramolecular interactions and bioorganic chemistry, as well as novel or improved synthetic approaches.
Keywords: ds-DNA and ds-RNA binding; intercalation; minor groove binding; nucleic acids; organic synthesis; phenanthridine; phenanthridinium